2001
DOI: 10.1143/jjap.40.5271
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Selective Photoresist Ashing Process for Silicon Nitride Films by Addition of Trifluoromethane

Abstract: We reexamine the constrained version of the Next-to-Minimal Supersymmetric Standard Model with semi universal parameters at the GUT scale (CNMSSM). We include constraints from collider searches for Higgs and susy particles, upper bound on the relic density of dark matter, measurements of the muon anomalous magnetic moment and of Bphysics observables as well as direct searches for dark matter. We then study the prospects for direct detection of dark matter in large scale detectors and comment on the prospects f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Several studies have reported the formation of an AFS layer on SiN films using HFC and NH 3 /NF 3 -related plasmas. ,, Miyoshi et al used the formation of AFS through CH 2 F 2 /O 2 or CHF 3 /O 2 plasmas in the ALE process, combined with IR annealing to facilitate the sublimation of AFS. , In our study, we demonstrate a similar behavior by a different approach without the use of thermal irradiation. Figure illustrates an overview of the presented ALE and etching mechanism, based on the in situ FTIR and EPC results.…”
Section: Resultssupporting
confidence: 74%
“…Several studies have reported the formation of an AFS layer on SiN films using HFC and NH 3 /NF 3 -related plasmas. ,, Miyoshi et al used the formation of AFS through CH 2 F 2 /O 2 or CHF 3 /O 2 plasmas in the ALE process, combined with IR annealing to facilitate the sublimation of AFS. , In our study, we demonstrate a similar behavior by a different approach without the use of thermal irradiation. Figure illustrates an overview of the presented ALE and etching mechanism, based on the in situ FTIR and EPC results.…”
Section: Resultssupporting
confidence: 74%
“…As the H 2 concentration increased to 27%, the contribution of the N–H x component noticeably increased. A small component corresponding to the NH 4 + bond at binding energy around 402 eV, , indicative of the presence of the ammonia fluorosilicate (AFS), (NH 4 ) 2 SiF 6 phase, can also be observed. This observation is consistent with previous studies that used other hydrogen-contained fluorocarbon plasmas. , Furthermore, a peak at the low energy side, corresponding to the N–Si 3 bond (∼398 eV), is also observed.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously determined that ammonium hexafluorosilicate forms on the surface of Si3N4 film after exposure to CF4 plasma when the film surface is hydrogenated and oxygenated 18 . Subsequently, the detection of ammonium salt on Si3N4 after plasma was reported for various plasmas such as NF3/O2/NH3 19 , CF4/H2/O2 20 , and CHF3/O2 21 . An XPS study also reported that ammonium hexafluorosilicate formed on a plasma-exposed Si3N4 is eliminated after heating at 300 °C21 .…”
Section: Si3n4 and Tin Ale Selective To Sio2 And Poly-simentioning
confidence: 99%